Longitudinal association between body mass index and health-related quality of life - Müller-Nordhorn, Jacqueline; Muckelbauer, Rebecca; Englert, Heike; Grittner, Ulrike; Berger, Hendrike; Sonntag, Frank; Völler, Heinz; Prugger, Christof; Wegscheider, Karl; Katus, Hugo; Willich, Stefan N. (PLOS ONE, 2014)
Health-related quality of life (HRQoL) is an important outcome in individuals with a high risk for cardiovascular diseases. We investigated the association of HRQoL and body mass index (BMI) as an indicator for obesity.
Gesehen am 25.09.2020